The Effectiveness of SwishMax Learning Media in Improving the Understanding of Arabic Sentences in Class VIII at MTs Nurul Falah Lumajang in the Academic Year 2024/2025 - Fitriyah, Putri Ayu Nuzulul (Rausyan Fikri Journal of Islamic Studies, 2024)
The objectives of this research: To know the effectiveness of the teaching method Swish Max to improve the comprehension of Arabic sentences in the eighth grade at Nurul Falah Islamic Middle School, Lumajang for the academic year 2024/2025. The researcher used the quantitative research method with the experimental research type (Quasi Eksperimental Design). As for the data collection method, it was through tests, observation, interviews and documentation. In analyzing the data, the researcher used the descriptive statistical test, the normality test, the homogeneity test and the Independent Sample T-Test. In her analysis, the researcher was assisted by using the IBM SPSS Statistic 22 for Windows application.The result of this research: 1) Based on the results of teaching verbal and nominal sentences, using the teaching method Swish Max to improve the comprehension of Arabic sentences in the eighth grade at Nurul Falah Islamic Middle School Lumajang for the academic year 2024/2025 is effective. 2) In the nominal sentence in the Independent Sample T-Test, the result was T.History (2.283) and T.Table (2.010), with these results we know that T.History T.Table, therefore the optional hypothesis (Ha) is accepted. 3) In the verbal sentence in the Independent Sample T-Test, the result was T.History (2.126) and T.Table (2.010), with these results we know that T.History T.Table, therefore the optional hypothesis (Ha) is accepted.